Determinan Personal Financial Management Behavior pada Pelaku UMKM di Kecamatan Mranggen - Sugeng Riyanto; Uswatun Khasanah (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2025)
This study aims to analyze the influence of financial attitude, financial literacy, financial knowledge on personal financial management behavior through locus of control as an intervening variable on MSME actors in Mranggen District. Respondents in the study were MSME actors in the food and beverage sector in Mranggen District and the sample used was 70 MSMEs. The sampling technique used the purposive sampling method and the data analysis tool used SmartPLS version 4.0. Based on the results of the research test, it shows that financial attitude has a significant positive effect on locus of control, financial literacy has a negative but significant effect on locus of control, financial knowledge has a significant positive effect on locus of control, financial attitude has a significant positive effect on personal financial management behavior, financial literacy has a negative and insignificant effect on personal financial management behavior, financial knowledge has a significant positive effect on personal financial management behavior, locus of control has a significant positive effect on personal financial management behavior, financial attitude has a significant positive effect on personal management behavior through locus of control as an intervening variable, financial literacy has a negative effect on personal financial management behavior and financial knowledge has a positive and significant effect on personal financial management behavior.